2003
DOI: 10.1590/s1415-43662003000200026
|View full text |Cite
|
Sign up to set email alerts
|

Compósitos à base de cimento reforçados com polpa celulósica de bambu. Parte I: Determinação do teor de reforço ótimo

Abstract: Este trabalho apresenta os resultados experimentais de um estudo em que se procurou desenvolver compósitos de matriz cimentícia reforçada com polpa de bambu. Foram usados dois tipos de polpa: refinada e sem refino. Fez-se variar o teor de fibras de 0 a 16% em massa de cimento e se desenvolveu um processo com sucção, moldagem e prensagem para fabricação dos compósitos. As relações constitutivas dos compósitos foram definidas através de ensaio a compressão e tração de corpos-de-prova cilíndricos de 5x10 cm e do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
2
3
0
2
Order By: Relevance
“…Possibly, for lower quantities, there is a reduction in the modulus of rupture by the insufficient amount of fibers and, for higher quantities, due to the loss dispersion caused by a large amount of fiber. This same trend was observed in studies conducted by [31]. According to Figs.…”
Section: Modulus Of Rupturesupporting
confidence: 88%
“…Possibly, for lower quantities, there is a reduction in the modulus of rupture by the insufficient amount of fibers and, for higher quantities, due to the loss dispersion caused by a large amount of fiber. This same trend was observed in studies conducted by [31]. According to Figs.…”
Section: Modulus Of Rupturesupporting
confidence: 88%
“…This observation indicates improved adherence of the fibers with the matrix for the F22AN composite, which is consistent with both the MOR (Table 5) and the difference of the mechanisms for failure described above. The results obtained in this work were improved compared to those reported by Dos Anjos et al 83 To verify either the presence of Ca originating from the cementitious matrix or the permanence or loss of the coating in the case of the composites made with F22AN fibers, a portion of the fibers at the point of failure of the failed test specimens was removed and examined. The variations of some elements in the F22AN fiber before and after contact with the cement matrix are described in Table 4.…”
Section: ■ Introductionmentioning
confidence: 52%
“…The fracture for composites made with F12 fibers is most likely caused by the failure of the interface between the fiber and the matrix (loss of adhesion). Mohr et al 57 reports that the loss of adhesion can be favored by a weak interfacial zone, which can impart less friction during ductile fiber pull out, 57 because this mechanism dissipates more energy than the mechanism due to breakage of the fiber, as reported by Dos Anjos et al 83 This behavior is also indicated by the high values of the energy ductility index and the pull out zones observed in the SEM micrographs (Figure 8g). The failure pattern for the F22AN composite (Figure 8b) is a centered trough, with the sample generating less cracks than the composite with F12 fibers.…”
Section: ■ Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…Neste sentido, um dos grandes problemas com que se deparam as populações dos países em desenvolvimento é a falta de habitações dignas em virtude, principalmente, dos elevados preços dos materiais de construção (Lima Júnior et al, 2003); surge, então a necessidade de se utilizar materiais alternativos que sejam ecológicos, de baixo custo e com disponibilidade local (Anjos et al, 2003b), de modo a baratear os custos das habitações.…”
Section: Introductionunclassified